Modelling the drivers of cloud computing use for SME businesses - Hassan, Haslinda; Khairudin, Norhaiza; Mohd Nasir, Mohd Herry; Adon, Iskandar; Ismail, Noor Azizi (2015)
This study proposes a model of the drivers of cloud computing use for small and medium enterprises (SMEs) in Malaysia.The research model is developed based on technology-organization-environment (TOE) framework and diffusion of innovation (DOI) theory.It is proposed that the use of cloud computing is being influenced by relative advantage, compatibility, and complexity (from the technological context), CEO’s innovativeness, top management support, and technology readiness (from the organizational context), and competitive pressure (from the environmental context).A sequential explanatory mixed methods is used for data collection.The findings will contribute to knowledge in cloud computing, especially in regards to cloudbased technologies used by the SMEs and the drivers of use. The findings will also assist the government agencies in accelerating the use of cloud computing among the SMEs and extending the full benefits of cloud computing to sustain the competitiveness of the SMEs.